Global Financing Facility in Support of Every Woman Every Child - Kim, Jim Yong (2016)
The Global Financing Facility (GFF) in support of Every Woman Every Child, was launched at the Third International Conference on Financing for Development in July 2015. The facility helps close the funding gap for reproductive, maternal, newborn, child, and adolescent health, to provide smart, scaled and sustainable financing to accelerate efforts to end preventable maternal, newborn, child and adolescent deaths by 2030. Jim Yong Kim, President of the World Bank Group, strongly believes that healthy women and children enable healthy economies, political stability and forward momentum. They are our smartest investment, when we invest wisely.